Nutrition and Oral Medicine - Touger-Decker, Riva; Mobley, Connie; Epstein, Joel B. (Nutrition and Health, 2014)
Nutrition and Oral Medicine, Second Edition addresses the complex, multifaceted relationships between nutrition and oral health, explores proposed relationships between oral, systemic and nutritional well-being and provides insights into interprofessional, comprehensive care for individuals.  Chapters focus on diet, nutrition and oral health promotion and disease prevention across the lifespan, oral and dental diseases and disorders, oral manifestations of systemic diseases, and discussions of the synergy between oral tissues and nutrients.  Cutting edge research issues regarding the relationship of individual antioxidants, trace elements, polyphenols and other nutrient substrates and oral health/disease, nutrigenomics, screening for nutrition and oral risk and other areas are covered in detail. Editors and authors include experts in nutrition and oral health from around the world.  Nutrition and Oral Medicine, Second Edition is a invaluable resource for  health professionals in the fields of nutrition and dentistry as well as other disciplines whose research, practice and education includes nutrition and oral medicine.   It is an excellent resource for graduate level nutrition and dental students, dental and nutrition practitioners, educators and researchers as well as other health professionals.